Konflik Antar Etnik-Agama Dan Pembangunan Perdamaian Di Lombok: Sebuah Eksplorasi Everyday Peace Di Lombok Utara - Anam, Syaiful; Handayani, Nilam; Khairurrizki, Khairurrizki (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2024)
This article explores the concept of "Everyday Peace" in North Lombok, Indonesia, focusing on how this diverse region maintains ethno-religious harmony. Drawing upon Roger Mac Ginty's concept of "everyday peace," the study highlights the crucial role of local actors, rather than international interventions, in peacebuilding through daily routines, norms, and community interactions. North Lombok, despite its religious and ethnic diversity, has successfully avoided conflicts often seen in other parts of Lombok. Key factors contributing to this peace include the acceptance of differences, freedom of worship, and connectivity through interfaith collaboration. The article illustrates how local communities, youth groups, traditional leaders, and the government work together to promote tolerance, with religious festivals and community events serving as platforms for peaceful coexistence.  Employing an explanatory research method, the study investigates the cause-and-effect relationships within this social phenomenon, elucidating the observed dynamics by illustrating the positions and relationships between variables based on factual field observations. This approach goes beyond mere description, providing evidence for various possible explanations within the phenomenon. Primary data collection involves direct engagement in the field through observation, interviews, and questionnaires, while secondary data is sourced from reputable books, journals, and websites relevant to the research topic. The study concludes that everyday peace, rooted in local traditions and mutual respect, is a viable model for managing diversity and preventing conflict in multicultural societies. This approach, integrating local values and international frameworks, offers valuable insights for peacebuilding in other heterogeneous regions.